Rancangan Model Speed Brake Flaps Tipe Clamsheel sebagai Alat Peraga di Prodi Teknik Pesawat Udara Sekolah Tinggi Penerbangan Indonesia - Louis Latif, Hendri; Kuntoaji, Wahyu (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
Seeing the development of technology in the world of aviation at this time felt very rapidly, this must also be accompanied by practical tools that must follow the development of these technologies to support teaching and learning activities. To support teaching and learning activities, therefore the author intends to make modeling of teaching aids speed brake flaps found on an aircraft, and introducing the speed brake flaps system found on an aircraft and can also provide an overview of the flight control system regarding speed brake flaps so that the teaching process can be successful in accordance with the objectives of the syllabus, namely students have the ability to can understand the basic principles of aircraft structure and have the basic ability to perform maintenance, because so far students can only imagine never seeing directly the tools being learned. seed brake is a type of flight control surface used on aircraft to increase drag (drag). This speed brake simulation provides an overview of the operation and mechanism of action of a speed brake. This design was made with a simple system to facilitate operation. In the designer, the method used is the library method using literature books and experimental methods. Because it is only as a prop, the hydraulic pressure needed is low. The hydraulic pressure used to operate the design of this trainer is 90 psi with a load on the mechanical system of 160.83 lbs. The electric current source used to operate the design of this teaching aid is 220V AC to start an electric motor with 1 HP power so that it rotates the gear type hydraulic pump which produces pressurized fluid for operation. It takes a power of 766 Watt to operate the design of these Trainer.